Evaluasi Struktur Gaji dan Skala Upah (SSU) Berdasarkan Point System Method pada UKM Pondok Nasi Kapau Uni As Reformasi - Afrida, Adilah Difa; Miadi, Dioba Pinkan Kirani Putri; Kristianingsih, Jesia Nathaniela; Dewi, Nandita Aulya; Dahifo, Rizka Aulia Feriza; Kartika, Lindawati (Economic Reviews Journal, 2024)
Pondok Nasi Kapau Uni As Reformasi is an SME operating in the food industry and was established in 1998. This study aims to analyze the compensation system at SME Pondok Nasi Kapau Uni As Reformasi. Primary data was obtained from the owner, manager, and several employees. While secondary data is collected from scientific journals, books, and relevant literature using descriptive analysis method to evaluate the compensation system in UKM Pondok Nasi Kapau Uni As Reformasi. The data analysis method is used to determine compensation factors that can be offset using the hay method approach. Revamping the salary structure is needed at UKM Pondok Nasi Kapau Uni As Reformasi to achieve an ideal compensation model. The multiple scale method was used in the preparation of the new salary mapping, with a spread value greater than mid-to-mid. The results show that the overlapping multiple scale method is more efficient because there is no significant change to the salary and the new total salary is not significantly different from the old total salary.